Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Matematika Pada Materi Operasi Hitung Pembagian di Sekolah Dasar - Anggita Putri Alystia; Isrokatun Isrokatun; Riana Irawati (Universitas Negeri Padang, 2024)
The purpose of this study was to describe the errors made by pupils when solving math narrative problems based on Newman's procedure involving division calculations. This qualitative study employed a descriptive methodology. Six students from class IV-C at SDN Cipayung 1 Depok served as research participants. Random purposeful sampling was utilized to select the subjects. Exams and interviews served as the instruments. Data analysis steps include data reduction, data presentation, and conclusion concluding. According to the research findings, students are prone to committing multiple types of errors when solving math narrative problems involving division arithmetic operations. These include process skills errors, reading errors, transformation errors, comprehension errors, and writing errors in the final solution. The factors that cause students to make mistakes include confusion, shortening time, accuracy, writing, and students' understanding of division calculation operations.